Study of a stall induced dynamical system under gust using the probability density evolution technique. (1st January 2016) - Devathi, Harshini; Sarkar, Sunetra
Highlights: Stall flutter system under random gust is studied. Gust is discretized using a Karhunen–Loeve expansion. Stochastic response surface shows irregular behaviour. Probability density evolution method (PDEM) has been used. PDEM gives higher accuracy than polynomial chaos expansion method. Abstract: Stall induced oscillations are likely instabilities in modern wind engineering systems. For their robust design, it is crucial to take parametric and load uncertainties into consideration. Presently, study of a stall flutter system under the influence of random gust is undertaken using the probability density evolution method, and qualitative changes in the response output are presented. This probability based approach when compared with a spectral tool called polynomial chaos expansion, shows better accuracy for the same level of discretisation.